The Red Sea Simulator: A high‐precision climate change mesocosm with automated monitoring for the long‐term study of coral reef organisms. (3rd May 2018) - Bellworthy, Jessica; Fine, Maoz
Abstract: Experimental systems that enable the controlled perturbation of environmental parameters toward future scenarios are in high demand and becoming increasingly advanced. Herein, we describe the design and assess the performance of a large‐scale, flow‐through, mesocosm system. Located in the northern Gulf of Aqaba, the Red Sea simulator (RSS) was constructed in order to expose local coral reef organisms to future ocean scenarios. Seawater temperature and pH are typically set to a delta from incoming seawater readings and thus follow the diel range. This is achieved through automated monitoring (sensor‐carrying robot) and feedback system and a remote‐controlled user interface. Up to six different temperatures and four pH scenarios can be concomitantly operated in a total of 80 experimental aquaria. In addition, the RSS currently facilitates the manipulation of light intensity, light spectra, nutrient concentration, flow, and feeding regime. Monitoring data show that the system performs well; meeting the user‐defined environmental settings. A variety of reef organisms have been housed in the system for several months. Brooding reef building and soft coral species maintained in the simulator for many months have released planulae in synchrony with field colonies. This system boasts a high degree of replication, potential for multistressor manipulation, typical physiochemical environmental variability, and remotely controlled monitoring and data acquisition. These aspects greatly enhance our ability to make ecologically relevant performance assessments in a changing world.